Poly(asparagine)-modified duplex stainless steel composite carbon paste electrode for selective electrochemical detection of dopamine - Rajendrachari, Shashanka; Nagarajappa, Hareesha; Neelalochana, Varun Donnakatte; Shivaraju, Rakshitha Gattavadipura; Demir, Ersin; Antherjanam, Santhy; Karaoglanli, Kazim Erden (Int Assoc Physical Chemists-Iapc, 2026)
Dopamine (DA) is a vital neurotransmitter used in clinical diagnostics and neurochemical studies. In this article, a robust, accurate, and highly sensitive method for determining DA using a duplex stainless steel (DSS)-modified carbon paste electrode (MCPE) and cyclic voltammetry is reported. To improve the sensitivity of the DSS-MCPE, the electrode was polymerized via 10 potential cycles using asparagine, a non-essential amino acid, thereby forming poly(asparagine) on the electrode surface. This polymerized electrode surface acts as a selective barrier to DA and enables the DSS-MCPE to detect DA accurately, even in the presence of interfering molecules such as ascorbic and uric acids, which have overlapping oxidation potentials. Compared with the bare carbon paste electrode (BCPE) and DSS-MCPE, poly(asp)-DSS-MCPE exhibits excellent electrochemical behaviour, a higher oxidation peak current, and improved electron transfer kinetics. The effects of variations in scan rate, pH, and DA concentration on the electrocatalytic behaviour of poly(asp)-DSS-MCPE were investigated. Also, the electrode active surface area was calculated, and the limit of detection, limit of quantification, and number of electrons and protons involved in electrochemical reactions were determined. The ease of fabrication, cost-effectiveness, and robust performance of poly(asp)-DSS-MCPE make it a promising electrocatalyst for detecting DA and other bioactive molecules, without interference from interfering molecules.
Keywords: Catecholamine; Voltametric Determination; Mechanical Alloying; Modified Electrode; Asparagine